Ajwain (Trachyspermum ammi L. Sprague) based intercropping for higher system productivity of semiarid tropics of Northern Karnataka: Ajwain based intercropping - Asangi, Honnappa; Kattimani, K N; Mastiholi, A B; Siddappa, R; Harisha, C B (Journal of Spices and Aromatic Crops, 2023)
Field trials were executed at the University of Horticultural Sciences, Bagalkot, Karnataka during the kharif season of 2016 and 2017 to study the growth and productivity of ajwain and leafy vegetables under intercropping system including economic profitability of such cropping systems in Northern Karnataka. The experiments were carried out with thirteen treatments comprising sole ajwain and sole crops of leafy vegetables (fenugreek, coriander, dill and amaranthus) and various combinations of ajwain and leafy vegetables in 1:1 and 1:2 ratios adopting randomized complete block design with three replications. Results showed that the sole crop of ajwain exhibited superior growth and yield. However, in intercropping systems, the combination of ajwain and coriander at a 1:1 ratio demonstrated the highest growth and yield parameters. The sole crop of ajwain recorded the maximum plant height (84.64 and 84.55 cm), number of branches per plant (52.38 and 52.19), number of umbels per plant (166.54 and 164.93), number of umbellate per umbel (12.44 and 12.34), and seed yield (12.95, 12.88 q ha-1 during both the years, respectively). This performance was comparable to intercropping with ajwain + coriander (1:1). Sole crops of fenugreek, coriander, dill, and amaranthus yielded higher fresh market yields compared to different intercropping systems. Notably, growing ajwain as an intercrop with coriander at a (1:1) resulted in a significantly higher land equivalent ratio (1.61) and a higher benefit–cost ratio (2.99) followed by ajwain + fenugreek (1:1) (2.98).